Progressive Enrichment of Stemness Features and Tumor Stromal Alterations in Multistep Hepatocarcinogenesis - Yoo, Jeong Eun; Kim, Young-Joo; Rhee, Hyungjin; Kim, Haeryoung; Ahn, Ei Yong; Choi, Jin Sub; Roncalli, Massimo; Park, Young Nyun (PUBLIC LIBRARY SCIENCE, 2017)
Cancer stem cells (CSCs), a subset of tumor cells, contribute to an aggressive biological behavior, which is also affected by the tumor stroma. Despite the role of CSCs and the tumor stroma in hepatocellular carcinoma (HCC), features of stemness have not yet been studied in relation to tumor stromal alterations in multistep hepatocarcinogenesis. We investigated the expression status of stemness markers and tumor stromal changes in B viral carcinogenesis, which is the main etiology of HCC in Asia. Stemness features of tumoral hepatocytes (EpCAM, K19, Oct3/4, c-KIT, c-MET, and CD133), and tumor stromal cells expressing alpha-smooth muscle actin (alpha-SMA), CD68, CD163, and IL-6 were analyzed in 36 low grade dysplastic nodules (DNs), 48 high grade DNs, 30 early HCCs (eHCCs), and 51 progressed HCCs (pHCCs) by immunohistochemistry or real-time PCR. Stemness features (EpCAM and K19 in particular) were progressively acquired during hepatocarcinogenesis in combination with enrichment of stromal cells (CAFs, TAMs, IL-6+ cells). Stemness features were seen sporadically in DNs, more consistent in eHCCs, and peaked in pHCCs. Likewise, stromal cells were discernable in DNs, showed up as consistent cell densities in eHCCs and peaked in pHCCs. The stemness features and tumor stromal alterations also peaked in less differentiated or larger HCCs. In conclusion, progression of B viral multistep hepatocarcinogenesis is characterized by an enrichment of stemness features of neoplastic hepatocytes and a parallel alteration of the tumor stroma. The modulation of neoplastic hepatocytes and stromal cells was at low levels in precancerous lesions (DNs), consistently increased in incipient cancer (eHCCs) and peaked in pHCCs. Thus, in B viral hepatocarcinogenesis, interactions between CSCs and the tumor stroma, although starting early, seem to play a major role in tumor progression.
Keywords: HEPATOCELLULAR-CARCINOMA; LIVER-CANCER; PROMOTE; CELLS; MICROENVIRONMENT; HEPATOCYTES; EXPRESSION; NODULES; ANTIGEN